Chemoenzymatic Synthesis of ABC-Type Enantiostructured Triacylglycerols by the Use of the p-Methoxybenzyl Protective Group - Hafdis Haraldsdottir; Haraldur G. Gudmundsson; Kaisa M. Linderborg; Baoru Yang; Gudmundur G. Haraldsson (Molecules, 2024)
This report demonstrates the first asymmetric synthesis of enantiopure structured triacylglycerols (TAGs) of the ABC type presenting three non-identical fatty acids, two of which are unsaturated. The unsaturated fatty acids included monounsaturated oleic acid (C18:1 n-9) and polyunsaturated linoleic acid (C18:2 n-6). This was accomplished by a six-step chemoenzymatic approach starting from (R)- and (S)-solketals. The highly regioselective immobilized Candida antarctica lipase (CAL-B) played a crucial role in the regiocontrol of the synthesis. The synthesis also benefited from the use of the p-methoxybenzyl (PMB) ether protective group, which enabled the incorporation of two different unsaturated fatty acids into the glycerol skeleton. The total of six such TAGs were prepared, four constituting the unsaturated fatty acids in the sn-1 and sn-2 positions, with a saturated fatty acid in the remaining sn-3 position of the glycerol backbone. In the two remaining TAGs, the different unsaturated fatty acids accommodated the sn-1 and sn-3 end positions, with the saturated fatty acid present in the sn-2 position. Enantiopure TAGs are urgently demanded as standards for the enantiospecific analysis of intact TAGs in fats and oils.